Influence of social context on the use of communication strategies among TESL undergraduates in UNIMAS - Jennifer, Sim Sing Ee. (Universiti Malaysia Sarawak, UNIMAS, 2007)
Communication strategies (CS) are strategies used by the speakers to overcome linguistic inadequacies in their communication and to enhance negotiation of meaning in interaction. This study investigates the influence of social context on the use of communication strategies. It examines the types of CS used by the TESL undergraduates in UNIMAS in three different contexts, namely, presentation, discussion and casual conversation. It also studies how the types of CS are associated with certain language functions in order to achieve communication purposes. The utterances of 25 TESL undergraduates in the three contexts were audiorecorded in natural settings, transcribed and analysed in light of the interactional perspective of CS (Tarone, 1978) and the pragmatic perspective (Clennell, 1995). The findings of the study indicate that social context does influence the use of CS, particularly, in the use of CS as communication-problem- solving device. In the presentation, only target- language based CS, prominently, restructuring, were used. On the other hand, language switch and restructuring dominates the data set in the discussion. As for casual conversation, language switch is extensively used. The use of language switch mounts as the context shift from formal to informal along the continuum. The result that reveals the greater use of CS to enhance message than to overcome communicati on difficulties also lends supports to Clennell’s suggestion to expand the functions of CS by recognising its use as message enhancer in lieu of the its sole function on resolving communication problems. Overall, the discourse-based strategies were used mainly to mark key information whereas the avoidance strategies were resorted in the participants’ attempts to avoid unknown concept. In order to gain thinking times, fillers or hesitation devices as well as the lexical repetition were sought. Additionally, lexical repetition, offering help and appealing for assistance were used to maintain conversational topic besides retaining an interaction.